Teacher Motivation: A Potent Factor for Promoting Excellence in Teaching and Learning in Secondary Schools in Nigeria - UMEOZOR, Juliana (International Journal of Educational Management, 2025)
Teachers are potent factors in the teaching and learning environment whose significant contributions towards impacting on students’ learning will always lead to national development in the society. It has been confirmed through various researches that teachers are important machineries that stand at the forefront of students’ learning. Given the important of teachers in the secondary schools, anything that will make them not committed or dedicated for excellent performances on their jobs should be avoided. On this premise, teacher motivation becomes a potent factor in the teaching and learning situations. This paper however examined issues concerning teacher motivation as a potent factor for promoting excellence in teaching and learning in secondary schools in Nigeria. Several terms such as motivation, teacher motivation and types, teaching and learning, and excellence were defined in the paper; and the criteria of excellent teaching which warrants teacher motivation in the secondary schools was discussed as well. The important benefits of teacher motivation as a potent factor in promoting excellence in teaching and learning in the secondary schools were discussed in the paper. Few empirical studies were also cited in the paper in order to showcase the importance of teacher motivation in promoting excellence in teaching and learning. Further highlighted in the paper were the strategies for teacher motivation and empowerment. The paper was concluded by determining such factors that hindered effective utilization of teacher motivation in order to promote excellence in teaching and learning in the Nigerian secondary schools.